Internal audit in the federal organizations of Malaysia: Is there light at the end of the long dark tunnel? - Md Ali, Azham; Ahmi, Aidi; Ali, Amin; Ghazali, Mohamad Zulkurnai; Gloeck, Jd; Lee, Th (SAIGA, 2009)
Internal audit is supposed to help members of organizations to improve their business activities.But the findings from in-depth interviews with internal auditors from a total of 40 federal government ministries, departments and agencies in Malaysia, conducted in the middle of 2004, have revealed a number of serious shortcomings. Most notable of these shortcomings are that many internal audit units have a shortage of staff, and that the audit staff lack internal audit skills.In addition, a majority of the audit units still employ outdated audit practices, and have failed to get the right level of support and assistance from the Treasury.Worse still, their operational effectiveness and efficiency is threatened by the high-handed conduct of the National Audit Department which arbitrarily and unilaterally shuffles staff between the body and internal audit units.With national and pubic sector surrounding leaving much to be desired for in regard to transparency and public accountability of the major actors and the fact that Malaysia is a large power distance society, it may not be too far fetch to expect the internal audit quagmire to continue to take place into the foreseeable future.